Managerial competence of school principals in improving the quality of elementary education services - Wiwit Yuliesie Rasyid; Ila Rosmilawati; Jakaria (Lentera Negeri, 2026)
This study examined the managerial competence of elementary school principals in improving educational service quality in Lebak Regency. A paradox was identified between two schools: one successfully transformed limited resources into high service quality and student achievement, while the other remained in a transitional phase. The research aimed to analyze the implementation of the personality, social, and professional dimensions of principals’ managerial competence in mobilizing the Standards for Educators and Educational Personnel and its implications for service quality and student achievement. A qualitative descriptive approach with a comparative case study design was employed. Data were collected through in-depth interviews, observation, and documentation involving principals, teachers, and the local education office, then analyzed using the interactive model of Miles and Huberman with source and technique triangulation. The findings showed that the principals applied a power-with approach, calm presence modeling, data-driven instructional leadership, optimization of non-permanent teachers based on competence, and dialogical clinical supervision. These practices improved teachers’ pedagogical competence, created a conducive learning environment, and enhanced student achievements up to the national level. The study concluded that principals’ managerial competence is the primary factor in continuous quality improvement in elementary schools, even under resource constraints.